Low-threshold transient calcium current in rat hippocampal lacunosum- moleculare interneurons: kinetics and modulation by neurotransmitters - Fraser, DD (J Neurosci, 1991)
Interneurons from the CA1 lacunosum-moleculare (L-M) region were isolated by trypsin-hyaluronidase treatment and mechanical trituration of the L-M. Interneurons isolated in this manner were multipolar with several dendritic processes and could be distinguished from CA1 pyramidal neurons. The properties of a low-threshold transient (LTT) Ca2+ current were investigated using whole-cell voltage-clamp techniques. The activation threshold of the LTT Ca2+ current was -60 mV, and the peak current, 100 +/- 9 pA (mean +/- SEM; n = 15), was observed at -30 mV. Ca2+ was the predominant charge carrier because the current was not affected by tetrodotoxin and was abolished in Ca(2+)- free external solution. Steady state inactivation was observed when the holding potential was positive to -100 mV, and the current was half- inactivated at -84 mV. Complete inactivation occurred at a holding potential of -60 mV. The time-to-peak of the current was highly voltage dependent and ranged from 10 msec at -60 mV to 4 msec at 0 mV. The time constant of inactivation was also voltage dependent and ranged from 27 msec at -60 mV to 12 msec at greater than -30 mV. Recovery from inactivation to 90% of maximum current occurred within 200 msec. L-M interneurons receive synaptic inputs from the septum that release ACh or GABA and from the raphe nuclei that release 5-HT. Carbachol, a nonhydrolyzable cholinergic agonist, and 5-HT quickly and reversibly increased the amplitude of the LTT Ca2+ current. Carbachol's actions were blocked by atropine, indicating that this effect was mediated by muscarinic receptors.